Creative Flow and Physiologic States in Dancers During Performance - Jaque, S. Victoria; Thomson, Paula; Zaragoza, Jessica; Werner, Frances; Podeszwa, Jeff; Jacobs, Kristin (Frontiers in Psychology, 2020)
Capturing the physiologic creative flow experience in performers while on stage is seldom possible. Pre-professional and professional dancers (n = 60) participated in this ambulatory psychophysiology study that investigated heart rate and autonomic nervous system responses during three time periods: baseline rest, performance, post-performance rest. State flow experiences (global flow, challenge-skill balance, sense of control, and autotelic experience) were measured and compared with physiologic responses (heart rate, pre-ejection period [PEP], and root mean square of the standard deviation [RMSSD]). Dancers were then divided into high and low flow groupings. To gather these results, the psychophysiology laboratory travelled to the concert hall to collect data on dancers. In this study, dancers generally endorsed high autotelic flow, challenge-skill balance, sense of control, and global flow. During performance, the high autotelic group and high sense of control group had a higher distribution of dancers with co-inhibition of both ANS branches compared to the low autotelic and sense of control groups who employed more co-activation of both ANS branches. The findings add to the growing information about both branches of the ANS during creative flow responses.